Feline Troglostrongylosis: Current Epizootiology, Clinical Features, and Therapeutic Options - Crisi, Paolo E.; Di Cesare, Angela; Boari, Andrea (Frontiers in Veterinary Science, 2018)
Parasitic bronchopneumonia plays an important role in feline respiratory medicine, thus it is receiving growing attention by researchers and practitioners. In recent years, Troglostrongylus brevior, a lungworm usually infecting wild felids, has been recognized as an agent of the lower respiratory tract in domestic cats. In particular, as a likely consequence of a spill-over from wild reservoirs (e.g. the European wildcat), T. brevior infection is increasingly reported in cats from Mediterranean and Balkan countries. This parasitic nematode has an indirect life cycle, and its biology overlaps that of the better known “cat lungworm” Aelurostrongylus abstrusus. In fact, cases of co-infections caused by both lungworms are not infrequent in domestic cats. Knowledge on clinical features of troglostrongylosis is still incomplete. Available data indicates that clinical signs and radiographic evidence are severe especially in kittens and young cats, are non-specific and often overlap with those of other feline respiratory diseases, such as feline bronchial disease/asthma, or infectious pneumonia. These characteristics make a definitive diagnosis of troglostrongylosis challenging, this disease requires a timely ancillary therapy and an appropriate anthelminthic treatment. As feline troglostrongylosis is an emerging parasitic disease of domestic cats, it should be included in differential diagnosis for lower respiratory tract disease in cats from regions where this parasite is present but also where it is unexpected. This article reviews current knowledge on the pathogenic role of T. brevior in domestic cats and resulting respiratory illness, with a special focus on clinical aspects, diagnosis and management of the disease.